Profil Kadar Hemoglobin dan Indeks Eritrosit pada Penjual Ikan Bakar di Kota Palangkaraya - Fera Sartika; Dwi Purbayanti; Eny Lestari (Jurnal Surya Medika (JSM), 2019)
The process of fish by baking or burning using charcoal can produce toxic chemical compounds, one of which is a carbon monoxide (CO) compound. CO compounds can be inhaled into the lungs through the respiratory system in humans, thereby replacing the position of oxygen to bind to hemoglobin and consequently, the level of oxygen in the blood becomes reduced. The purpose of this study was to determine the profile of hemoglobin and erythrocyte indices of the grilled fish seller selling around Pahandut District, Palangka Raya City. The study was conducted with a purposive sampling technique and the number of samples in this study was 25 people. The results showed normal hemoglobin levels of 24 people and below the normal value of 1 person. Normal MCV values were 16 people, MCV below normal values were 9 people (36%). Normal MCH 21 people (84%), MCH under normal values 2 people (8%), normal MCHC 19 people (68%), MCHC below normal values 1 person (1%), MCHC more than normal values 5 people (20%). Profile and erythrocyte indices of 25 samples obtained normal hemoglobin levels of 24 people (96%) and hemoglobin levels below normal values of 1 person (4%). The results of 1 person (4%) cytitrocyte index were suspected of having microcytic hypochromic anemia which could be caused by iron deficiency, and 1 person (4%) of the type was suspected of having microcytichipchromic anemia.